An Update from the Clinical Affairs Portfolio - Alan Barkun (Canadian Journal of Gastroenterology)
The Clinical Affairs portfolio reflects the most direct interests of the majority of the membership and focuses on issues related to patient care. It encompasses the Endoscopy, Hepatobiliary/Transplant, Liaison, Pediatric, Practice Affairs and Regional Representation Committees. The portfolio is overseen by Dr Alan Barkun, Chair of Clinical Affairs. Its committees have been very busy spearheading a number of initiatives over the past six months, while contributing to a number of projects undertaken by other committees of the Canadian Association of Gastroenterology (CAG).